Biological soil crusts and how they might colonize other worlds: insights from these Brazilian ecosystem engineers. (6th May 2022) - Oliveira, Mateus Fernandes; Maciel-Silva, Adaíses Simone
Abstract: When bryophytes, lichens, eukaryotic algae, cyanobacteria, bacteria, and fungi live interacting intimately with the most superficial particles of the soil, they form a complex community of organisms called the biological soil crust (BSC or biocrust). These biocrusts occur predominantly in drylands, where they provide important ecological services such as soil aggregation, moisture retention, and nitrogen fixation. Unfortunately, many BSC communities remain poorly explored, especially in the tropics. This review summarizes studies about BSCs in Brazil, a tropical megadiverse country, and shows the importance of ecological, physiological, and taxonomic knowledge of biocrusts. We also compare Brazilian BSC communities with others around the world, describe why BSCs can be considered ecosystem engineers, and propose their use in the colonization of other worlds. Abstract : We summarize studies on biological soil crusts (BSCs) in Brazil and their relevance as ecosystem engineers. We also present uses of BSCs in the colonization of bare soils.